Impact of higher category infrastructure on public transport related to travel to work - Mondek, Norbert (CAL-TEK SRL, 2023)
Employee travel to work makes up a significant part of journeys in public and individual transport. Daily commuters often have a choice between several modes of transport. For the efficient use of public transport, the key task is its attractiveness and adequacy of the services provided with respect to the demand on a particular line. To do this, it is sometimes effective to bypass (large) cities located along the route of the line, in order to achieve the fastest possible travel time. It is in this context that the available higher-end infrastructure (bypasses) has a major impact, which is important not only for individual transport, but also, in some cases, for public transport. On the example of this article, it is shown that with a sufficiently strong transport session, it is expedient to bypass even the second largest city in the country. Public transport is monitored using transport modelling, which is an effective tool for forecasting future intensities in individual and public transport. By simulating various traffic scenarios, future traffic behaviour of passengers can be predicted with high accuracy. This modeling method is also used in this paper.
Vliv infrastruktury vyšší kategorie na veřejní dopravu v souvislosti s cestováním do práce
Keywords: Transport modelling; public transport; higher category infrastructure; Dopravní modelování; veřejná doprava, infrastruktura vyšší kategorie, mezilehlá sídla